The unsuspected circles. On the late recognition of southern Iberian Neolithic and Chalcolithic ditched enclosures - Jiménez-Jáimez, Víctor José (Cambridge University Press, 2015)
Neolithic ditched enclosures appear to be widely distributed across Central and Western Europe, and from the Mediterranean area to Scandinavia. They have been known in areas of Europe for a long time, but particularly in the last 25 years studies on British, French, Central European, and Scandinavian ditched enclosures have ﬂourished. In line with this, a number of international meetings occurred in the last three decades. In southern Iberia, by contrast, ditched enclosures only began to be known in the 1970s, and even then methodological deﬁciencies and lack of funding hampered their characterisation. As a consequence of this, Iberian Neolithic and Copper Age ditched enclosures were largely unknown outside Portugal and Spain. They were not represented in any of the international meetings above, nor included in any of the syntheses made about the topic. Not only that, for decades, Spanish and Portuguese archaeologists were not aware of the potential analogies themselves, and the research that was being carried out elsewhere in Europe had almost no inﬂuence on the way ditched enclosures were surveyed, excavated, and interpreted in the peninsula. The main objective of this article is to advance the recognition of the southern Iberian evidence by other European researchers and the integration of the Iberian conversation into the general discussion. The focus will be on how these sites have been studied by several generations of Iberian archaeologists, in an attempt to explain why it has taken Portuguese and Spanish archaeologists so long to realise that Iberian enclosures should not be understood in isolation.
Keywords: Fortificaciones - Historia - Europa; Arqueología; Prehistoria; Neolítico; Calcolítico; Península ibérica; Teledetección; Prospección geofísica; Recintos de fosos